Modest, not extreme, northern high latitude amplification over the Mid to Late Miocene shown by coccolith clumped isotopes - Mejia Ramirez, Luz Maria; Bernasconi, Stefano M.; id_orcid:0 000-0001-7672-8856; Fernandez, Alvaro; Zhang, Hongrui; Guitián, José; Jaggi, Madalina; Taylor, Victoria Emma; Perez-Huerta, Alberto; Stoll, Heather; id_orcid:0 000-0002-2953-7835 (EarthArXiv, 2024)
The ongoing global warming is characterized by a high latitude amplification effect, with Northern Hemisphere air temperatures increasing significantly faster than the global average. Widely-used paleotemperature proxies suggest that during past warm climate states, there was extreme high-latitude and polar amplified warming, along with flat latitudinal sea surface temperature (SST) gradients. Because these features remain difficult to simulate in climate models for periods like the Miocene, not only model construction, but also absolute values of proxy temperature estimates should be continuously revised. Clumped isotope thermometry is a tool that has the potential to bypass some of the limitations of other proxies, such as reliance on assumptions of past seawater chemistry, and other unknown mechanisms influencing their response to temperature changes. Here we provide the first downcore reconstruction of calcification temperatures from coccolith clumped isotopes (∆47) at northern high latitudes. This record shares trends with alkenone SSTs from the same samples estimated via widely-used calibrations, but suggest an on average ~9 °C colder North Atlantic over the last 16 million years (My). Coccolith ∆47 calcification temperatures agree better than alkenone-derived records with model simulations for the Mid and Late Miocene. If confirmed by additional records, a modest, rather than an extreme northern high latitude warmth, would entail paradigm-changing implications in our understanding of high latitude thermal response to anthropogenic CO2, while implying a need for revision of the present interpretations of currently considered well-validated temperature proxies like alkenone unsaturation ratios.